Structure-based design and application of an engineered glutathione transferase for the development of an optical biosensor for pesticides determination - Chronopoulou, Evangelia G.; Vlachakis, Dimitrios; Papageorgiou, Anastassios C.; Ataya, Farid S.; Labrou, Nikolaos E. (Biochimica et biophysica acta. General subjects, 2019)
In the present work, a structure-based design approach was used for the generation of a novel variant of synthetic glutathione transferase (PvGmGSTU) with higher sensitivity towards pesticides. Molecular modelling studies revealed Phe117 as a key residue that contributes to the formation of the hydrophobic binding site (H-site) and modulates the affinity of the enzyme towards xenobiotic compounds. Site-saturation mutagenesis of position Phe117 created a library of PvGmGSTU variants with altered kinetic and binding properties. Screening of the library against twenty-five different pesticides, showed that the mutant enzyme Phe117Ile displays 3-fold higher catalytic efficiency and exhibits increased affinity towards α-endosulfan, compared to the wild-type enzyme. Based on these catalytic features the mutant enzyme Phe117Ile was explored for the development of an optical biosensor for α-endosulfan. The enzyme was entrapped in alkosixylane sol-gel system in the presence of two pH indicators (bromocresol purple and phenol red). The sensing signal was based on the inhibition of the sol-gel entrapped GST, with subsequent decrease of released [H+] by the catalytic reaction, measured by sol–gel entrapped indicators. The assay response at 562 nm was linear in the range pH = 4–7. Linear calibration curves were obtained for α-endosulfan in the range of 0–30 μΜ. The reproducibility of the assay response, expressed by relative standard deviation, was in the order of 4.1% (N = 28). The method was successfully applied to the determination of α-endosulfan in real water samples without sample preparation steps. •A structure-based design approach was used for engineering a mutant GST.•The mutant Phe117Ile displayed higher sensitivity towards pesticides.•The mutant was explored for the development of a novel optical biosensor for α-endosulfan.•The method was applied in real water samples without sample preparation steps.